Ganhadeiras literárias : tecnologias editoriais de Deisiane Barbosa e Tatiana Nascimento - Santos, Josiane Alves dos (2024)
The plots of contemporary Brazilian literature have showcased a diversity of mediums used for literary publication, particularly the editorial technologies managed by Black female writers. Consequently, the main objective of this work was to identify the authors who publish independently as “ganhadeiras literárias”, presenting their projects and some literary excerpts from their works. The corpus of this study is composed of Deisiane Barbosa, with her work “Cartas a Tereza” (2021), alongside her editorial project Andarilha Edições, and the poet tatiana nascimento, with her work “Palavra Preta” (2021), who is responsible for the publishing house Padê Editorial. By reclaiming the image and the designation of “ganhadeiras” for the context of contemporary literary productions, I intended to weaken the colonial-origin designation and enhance it with new terms and concepts: the “tabuleiro” as an editorial technology for publication, the “alimento” marketed in written literature, and the “cabeça” that carries the tabuleiro as a source for intellectual and artistic production. The study highlighted experiences that showcase literary productions filled with a diversity of flavors, smells, and textures that enrich the publishing market, contemporary literature, and the diasporic Black imagination